How it all ends: A model for teaching paragraph ending sentences to L2 students - Thomas, Anuja; McCarthy, Philip; Ahmed, Khawlah; Kaddoura, Noor; Duran, Nicholas (Pegem Journal of Education and Instruction, 2022)
Although topic sentences have been widely researched, similar consideration for paragraph endings has been less forthcoming. This discrepancy may be problematic as research suggests that instruction on textual endings can positively impact student writing. With this issue in mind, the current study establishes a model for paragraph endings and discusses pedagogical and computational implications. The model stems from the categorization of the varieties of paragraph endings observed in a corpus of papers written by advanced ESL college-students in the Arabian Peninsula. We identified the varieties of paragraph endings to form a multi-dimensional model featuring the categories of ‘goal,’ ‘type,’ and ‘cue.’ ‘Goal’ refers to the function of the sentence (e.g., summarizing). ‘Type’ refers to whether the sentence is a claim or a support statement. ‘Cue’ refers to explicit language indicating the goal. The model was assessed quantitatively through inter-rater-reliability of expert-judge evaluations. Qualitative analysis was also incorporated to assess possible subjective differences. Quantitative analysis provided validation of the model. Specifically, even with the most conservative analysis, the findings show that 67.5% of the total assessments were in agreement, with 75% agreement for goal and 70% agreement for type. The subsequent qualitative analysis also broadly supported the quantitative findings. We conclude that the validated model has viable implications for pedagogical practices and software development. Thus, the study provides a pathway that may benefit students in the writing of more effective paragraphs.